Livelihood Transformation of Agrarian Communities under Peri-Urban Housing Development: A Qualitative Review of Moncongloe Village - Nasrul Haq; S. Sakaria; S. Sultan (Golden Ratio of Mapping Idea and Literature Format, 2026)
Housing development in peri-urban areas has accelerated land-use change and reshaped the livelihoods of agrarian communities in Indonesia. This article aims to examine how housing development influences livelihood transformation in Moncongloe Village, Maros Regency, through a qualitative review of relevant theories and literature. The study employs a qualitative review approach based on literature analysis and conceptual synthesis, integrating perspectives from social change theory, development sociology, structural transformation, urbanization, and agrarian political economy. The review identifies three major findings. First, the conversion of agricultural land into residential areas reduces farming-based livelihoods and accelerates occupational shifts toward informal trade and service sectors. Second, although rising land values create short-term economic opportunities, they also increase long-term livelihood vulnerability for households with limited skills and adaptive capacity. Third, housing development reshapes social relations by weakening traditional agrarian solidarity, transforming local value systems, and creating unequal access to economic resources. These findings indicate that livelihood transformation in peri-urban areas extends beyond economic restructuring to encompass broader social and cultural changes. This study highlights the importance of integrating local capacity building into peri-urban development policies. Sustainable housing development should therefore balance physical expansion with strategies that strengthen community resilience, promote inclusive economic opportunities, and minimize the risk of structural marginalization among local residents.